KNOWLEDGE AS THE MANUFACTURE FACTOR - Natalia V. Tikhomirova; Siarhei M. Malchenka; Anatoli P. Yakimakho (Статистика и экономика, 2016)
This work demonstrates that in the knowledge-based economy knowledgebecomes the main manufacture factor. Without knowledge no man-made material and non-material objects can be created. Approaches to calculating the cost of knowledge capitalized in such objectsare deﬁned.